2002
DOI: 10.1525/ac.2002.13.1.42
|View full text |Cite
|
Sign up to set email alerts
|

How Magic Works: New Zealand Feminist Witches' Theories of Ritual Action

Abstract: The paper draws on three years' fieldwork and twelve years' familiarity withfeminist witches in New Zealand. These women are thoughtful and articulate about their magical practice, and it is their theories about how magic works and the function of ritual-making which are the paper's central concern. Scholarly theories and debates about magic and ritual have frequently been dichotomously constructed: science versus magic, the symbolists versus the intellectualists, causality versus participation, ritual as acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 7 publications
0
7
0
1
Order By: Relevance
“…Societies of the global North remain suffused with magic, spiritualism, witchcraft and the occult (Comaroff & Comaroff, 1999). There are degrees by which individuals in all societies may hold the supposedly dissected worldviews of the scientific and the spiritual, magical or religious, evidenced by the persistence of the fantastic (including magical animals) in popular culture (Rountree, 2002), and in major and minor religions, cults and witchcrafts (Moore & Sanders, 2001). Beliefs in magical animals are dynamic, and can transcend from the spiritual or mystical to become cultural heritage (Comaroff & Comaroff, 1999), such as the Loch Ness Monster, Welsh dragons and the Beast of Bodmin Moor in the UK, trolls in Denmark (Karrebæk & Maegaard, 2015), and various lake-dwelling monsters across the globe, including the Kanas Lake Monster in Xinjiang, China, the Seljordsormen in Norway, the Lagarfjót Worm in Iceland, and the Storsjöodjuret of Sweden (the latter was briefly given protected status by the Swedish Environmental Protection Agency but this was later revoked by the Swedish Parliament; Sandelin, 2014).…”
Section: Magic Animals and Contemporary Human Societiesmentioning
confidence: 99%
“…Societies of the global North remain suffused with magic, spiritualism, witchcraft and the occult (Comaroff & Comaroff, 1999). There are degrees by which individuals in all societies may hold the supposedly dissected worldviews of the scientific and the spiritual, magical or religious, evidenced by the persistence of the fantastic (including magical animals) in popular culture (Rountree, 2002), and in major and minor religions, cults and witchcrafts (Moore & Sanders, 2001). Beliefs in magical animals are dynamic, and can transcend from the spiritual or mystical to become cultural heritage (Comaroff & Comaroff, 1999), such as the Loch Ness Monster, Welsh dragons and the Beast of Bodmin Moor in the UK, trolls in Denmark (Karrebæk & Maegaard, 2015), and various lake-dwelling monsters across the globe, including the Kanas Lake Monster in Xinjiang, China, the Seljordsormen in Norway, the Lagarfjót Worm in Iceland, and the Storsjöodjuret of Sweden (the latter was briefly given protected status by the Swedish Environmental Protection Agency but this was later revoked by the Swedish Parliament; Sandelin, 2014).…”
Section: Magic Animals and Contemporary Human Societiesmentioning
confidence: 99%
“…Whilst witch hunts once were rampant across Europe, the last conviction for witchcraft in the UK in 1944 marked the terminus of official recognition of supernatural forces (Bukurura, 1994). However, the continued pervasiveness of the supernatural and fantastic has not gone unnoticed, including the preference for creationist over evolutionary accounts (Legare et al, 2012); the business of magic across literature, film and tourism (Rountree, 2002); interest in psychic phenomena;…”
Section: The Durability Of Witchcraft and Spiritual Worldviewsmentioning
confidence: 99%
“…One of the first studies in the anthropology of witchcraft, Evan-Pritchard's (1937) research on the Azande, suggested that Azande worldviews had an internal logical coherence. This was the inauguration of attempts to demark witchcraft as internally rational: a coherent worldview, logical in structure, where magic acts as a substitute for science, but also a social force moderating hierarchies and norms (Schram, 2010), an understanding which also aligns with symbolist logics of witchcraft as symbolic of social order (Rountree, 2002).Whilst both claims are functionalist (witchcraft performs a social function) and culturally relativist (witchcraft is logical 'from within'), they are substantiated through work demonstrating the social functions witchcraft and witchcraft accusations play (Kohnert, 1996). Witchcraft can act as a levelling force whereby individuals who outstrip their status are socially sanctioned (Geschiere, 1998), an idiom through which to interpret local inequality (Ciekawy, 1999).…”
Section: Witchcraft and Rationalitymentioning
confidence: 99%
See 1 more Smart Citation
“…As Rountree suggests of a group of feminist witches she worked with in New Zealand:
Central to their holistic worldview and their theories about magic's efficacy is the shamanistic belief that all things—plants, animals, people, rocks, the elements, and so on—are connected in dynamic relationship. (Rountree : 44)
…”
Section: Spirits and Deitiesmentioning
confidence: 99%